Dysphagia After Pediatric Laryngotracheal Reconstruction—A Scoping Review - Noor Singh; Stephen R. Chorney; Romaine F. Johnson; Taylor B. Teplitzky (Laryngoscope Investigative Otolaryngology, 2025)
ABSTRACT Objective To review swallowing outcomes after pediatric laryngotracheal reconstruction. Methods A scoping review was conducted through PubMed and Google Scholar databases for dysphagia outcomes after common pediatric airway surgery. Original full‐text articles written in English between 1987 and 2024 were included. Articles were excluded if data was unavailable to review or were not in English. Preferred reporting items for systematic reviews and meta‐analyses (PRISMA) Guidelines were followed. Results There were 31 articles included, which assessed swallowing after laryngotracheal reconstruction. Laryngotracheal reconstruction can result in transient post‐operative dysphagia, with the degree of severity related to preoperative swallowing status. Conclusion Most airway reconstructive surgery in children can be associated with postoperative dysphagia. However, the swallow dysfunction is typically transient and can be predicted by comorbidities or preoperative swallow function. Timely assessments and appropriate multidisciplinary interventions are essential to improve swallowing outcomes after pediatric laryngotracheal reconstruction. Level of Evidence 4.